“Cuidados de enfermería en paciente con insuficiencia respiratoria aguda intoxicado por estupefacientes” - Cerezo Ramirez, Ever Euclides (2024)
Acute respiratory failure is the inability of the respiratory system to efficiently carry out its primary function which is gas exchange, there will be a failure in the process of oxygen delivery and elimination of carbon dioxide from the body. This case study focused on applying nursing care in a patient with acute respiratory failure, intoxicated by narcotics, through a comprehensive nursing assessment to improve his health status. It was carried out by performing different techniques and fundamental methodological tools in the field of nursing, such as physical assessment and Marjory Gordon's eleven functional patterns. The patterns of health perception and management, as well as activity and exercise, were identified as priorities. In addition, NANDA, NOC and NIC taxonomy were used to establish diagnoses such as impaired gas exchange, ineffective respiratory pattern and risk of infection. Nursing interventions included respiratory monitoring, invasive mechanical ventilation management, airway management and infection protection. These actions were part of care plans designed to optimize patient health, especially respiratory status, and prevent possible complications.